The Tradition of Prohibiting Marriage during the Month of Suro in Purwajaya Village: A Study of Javanese Customary Practices in Lima Puluh Kota Regency - Hanifah, Wiwid; Nugraha, Rizky Firman; Hafizah, Mutia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study is motivated by the prohibition of marriage during the Suro month among the Javanese indigenous community in Purwajaya Village, Lima Puluh Kota Regency, while Islamic teachings do not prescribe any specific time for marriage. The study aims to analyze three main issues: first, the background of the prohibition of marriage during the Suro month among the Javanese community in Purwajaya Village; second, the values contained in this traditional prohibition; and third, the review of the practice from the perspective of Maqashid Shari’ah. This research employs an empirical approach using primary data obtained through interviews and documentation, which were then analyzed qualitatively within the framework of Maqashid Shari’ah. The findings indicate that the background of the prohibition is influenced by the perception that the Suro month is sacred and unsuitable for holding weddings, beliefs in potential misfortune, respect for ancestors, the influence of Kejawen philosophy, and the syncretism of Javanese culture with Islam. This tradition also contains several values, including religious, historical, social, and philosophical values, which serve as the foundation for the indigenous community in maintaining social harmony. From the perspective of Maqashid Shari’ah, the prohibition of marriage during the Suro month is inconsistent with the objectives of preserving religion, progeny, intellect, and wealth, as time restrictions without a Shari’ah basis can hinder the realization of greater benefits. The study underscores the dynamic interaction between cultural values and Maqashid Shari’ah principles and highlights the importance of a moderate approach in understanding local cultural practices that continue to thrive within society.